An enhanced strength Ni matrix composite reinforced by a 3D network structure of TiN nano-particles. (June 2020) - Wang, Rui; Zhu, Guoliang; Zhou, Wenzhe; Wang, Wei; Wang, Donghong; Dong, Anping; Shu, Da; Sun, Baode
Abstract: Strengthening is a critical issue for improving the mechanical properties of ceramic particles reinforced metal matrix composites (CPRMMCs). A Ni matrix composite reinforced by TiN nano-particles (TiNNP ) with a three-dimensional (3D) network structure was synthesized via low-energy ball-milling (LEBM) and spark plasma sintering (SPS). The ultimate tensile strength (UTS) of the TiN/Ni composite is 690 MPa, an increase of 383% compared to that of the Ni matrix. The 3D network structure of TiN nano-particles formed at the grain boundaries refines the grains significantly and generates a high density of dislocations near the TiN/Ni interface, synergistically contributing to the enhanced strength. Ceramic particles of 3D network structure may be a potential solution to achieving superior properties of CPRMMCs. Graphical abstract: Unlabelled Image